ANALYSIS OF BANKING GROWTH AFTER APPLICATION OF ASEAN ECONOMIC COMMUNITY. - Jajang Badruzaman, Irman Firmansyah (International Journal of Research Science and Management, 2018)
This study examines the differences in the growth of banking business in ASEAN before and after the entry into force of the ASEAN Economic Community (AEC). The variables studied are assets, third party funds and credit. The research period is growth in 2013 to 2014 (before AEC) and in 2016 to 2017 (after AEC). Data processing begins by reducing the three variables (assets, third party funds and credit) into a new variable using the Principal Component Analysis (PCA) and then doing a different test using the Wilcoxon signed rank test. The results showed that there was no difference in banking business growth between before and after the entry into force of the AEC. Therefore the banking sector has not been able to take advantage of the free market conditions in ASEAN, so it must continue to increase the opportunity to expand market networks in all ASEAN member countries in order to be able to improve its performance.